Ultra-slim flexible bronchoscopy-guided topical hemostatic drugs administration for the management of life-threatening refractory pulmonary hemorrhage in a preterm infant: Case report - Lin, Yan; Zhao, Hong-fang; Xue, Meng-hua; Xie, Bing-jie; Zeng, Ling-chao; Jiang, Xun (Frontiers in Pediatrics, 2022)
Pulmonary hemorrhage (PH) is a rare acute catastrophic event with high mortality among neonates, especially preterm infants. Primary treatments included pulmonary surfactant, high-frequency oscillatory ventilation (HFOV), epinephrine, coagulopathy management, and intermittent positive pressure ventilation. However, there are still challenges in diagnosing and treating refractory or focal pulmonary hemorrhages. Ultra-slim bronchoscopy has been widely used in the field of critically ill children and is increasingly being done in neonates with critical respiratory disease in recent years. In this study, we report a case with refractory pulmonary hemorrhage in premature infants, which was finally diagnosed as localized hemorrhage in the upper left lobe and cured by ultra-slim bronchoscopy-guided topical hemostatic drug administration. Bronchoscopy is an optional, safe, and practicable technique for early diagnosis and direct injection therapy of neonatal PH in managing life-threatening PH.